Pinkalicious and the pirates - Kann, Victoria (Kann, Victoria. Pinkalicious (HarperCollins (Firm)), 2018)
When Pinkalicious and Peter go to the hidden cove to meet their friend Aqua, a mini-mermaid, they see pirates instead.